Analysis of American Slang in The Movie of “The Blind Side” - Jakob, Juvrianto Chrissunday (Universitas Mathla'ul Anwar Banten, 2018)
Slang is an important feature in American culture. It is more effective than standard or conventional English, so I interested to discuss and classify of slang words in the movie of “The Blind Side”. The purpose of this research is to classify slang words in The Blind Side movie based on the characteristic on Andersson and Trudgill theory. This research used the descriptive qualitative method. The data source of this research is taken from the movie script of the movie of “The Blind Side” cited from IMDB. Based on the research result, there are 8 slang words or phrases in the movie of “The Blind Side”, the slang is divided into four categories: (1) 2 slang words or phrases as the neutral syntactic level; (2) 4 slang words or phrases as typical informal situations and (3) 2 slang words or phrases as creative.